Analysis of Physical Activity and Healthy Life Behavior in Physical Education Students during the Covid-19 Pandemic - Ahmad Ahmad Taufik Ali; Encep Sudirjo; Aam Ali Rahman (JUARA : Jurnal Olahraga, 2022)
This study aims to determine the Physical Activity and Healthy Lifestyle of Physical Education students during the Covid-19 pandemic. The method used in the research is a quantitative descriptive method with a survey research design. The population used in this study were PGSD Physical Education students, then the researchers used the Proportionate Stratified Random Sampling technique by determining a sample of 40 people. This study indicates that the physical activity variable produces three indicators, namely light, moderate and heavy physical activity, which can be obtained 17.5% on the excellent category, 45% in the excellent category, and 37.5% in the less category. So physical activity for physical education students during the COVID-19 pandemic is categorized as sufficient. The results of the healthy living behavior variable produce five indicators, namely behavior towards food and drink, personal habits, environmental hygiene, illness and disease and the balance between rest and sports activities can be obtained 7.5% excellent category, 25% good category, 40% moderate category, 15% in the poor class and 12.5% ​​in the inferior type. So the healthy living behavior of physical education students during the COVID-19 pandemic is categorized as sufficient. So that physical activity and healthy living behavior for physical education students during the COVID-19 pandemic both went quite well.